A55 LACK OF EXPERIMENTAL REPRODUCIBILITY IN PRECLINICAL RESEARCH IS INFLUENCED BY THE NUTRITIONAL PROFILE OF STANDARD RODENT CHOWS. (26th February 2020) - Tuck, C J; De Palma, G; Takami, K; Brant, B J; Caminero Fernandez, A; Reed, D E; Muir, J; Gibson, P; Winterborn, A; Bercik, P; Verdu, E; Vanner, S
Abstract: Background: Lack of experimental reproducibility, particularly in studies investigating the microbiota, is of growing concern to the scientific community. Factors such as environment, stress, and sex have been identified as contributors, whereas dietary composition has received less attention. Aims: To profile the use of standard rodent chows in research institutions, analyze the nutrient content of common rodent chows, and assess the impact of different chows on microbiota profiles. Methods: A survey was conducted to evaluate which rodent chows are used by research institutions worldwide. Seven standard rodent chows were selected for analysis of ingredients, fermentable carbohydrate (FODMAP) and gluten content. FODMAP content was measured by high-performance liquid-chromatography and enzymatic assays, and gluten content was assessed by a commercial kit using G12 antibody. Forty C57BL/6 mice were randomized to 4 groups of 10 mice (5 male, 5 female). Group A was euthanized at baseline. Group B received the breeding institution chow (LabDiet 5066). Group C received ResearchDiets AIN93G (low FODMAP and gluten content). Group D received LabDiet 5001 (high FODMAP and gluten content). After 3 weeks, cecal contents were collected and analyzed by 16S rRNA gene sequencing; short- and branched-chain fatty acids (SCFA, BCFAs) content was also determined. Results: Twenty-eight different types of rodent chows were reported to be used by 45 international survey respondents. Ingredient composition of the standard chows varied widely, resulting in differences in FODMAP and gluten content. Microbiota analysis of cecal contents revealed that gut microbiota composition was altered by the standard chows, as reflected by significantly different clusters in β-diversity analysis as well as by altered α-diversity. Microbiota diversity was also influenced by sex in Groups A and B ( p <0.01). Total SCFA levels were lower ( p =0.03) and BCFA levels were higher ( p =0.01) in Group C compared to Group B. Conclusions: Our results suggest that the composition of the diet not only significantly impacts gut microbiota profiles and fermentation patterns but may also emphasize sex differences in preclinical studies, with major implications for the reproducibility of results across laboratories. Funding Agencies: CIHRThe Canadian Nutrition Society